2004
DOI: 10.1073/pnas.0307190101
|View full text |Cite
|
Sign up to set email alerts
|

Loss of CDX1 expression in colorectal carcinoma: Promoter methylation, mutation, and loss of heterozygosity analyses of 37 cell lines

Abstract: Expression of the homeobox protein CDX1 is lost or reduced in a significant proportion of colorectal carcinomas (CRCs) but the underlying mechanism for this is unclear. We have demonstrated absence of CDX1 mRNA expression in 7 of 37 CRC cell lines and shown that all 7 cell lines have a methylated CDX1 promoter. Twenty-five cell lines showed both CDX1 mRNA expression and an unmethylated CDX1 promoter. The five remaining cell lines had a partially methylated CDX1 promoter and all expressed CDX1 mRNA; when treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
60
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 13 publications
5
60
1
Order By: Relevance
“…As suggested by Wong et al (19), selection for reduced expression of CDX1 by methylation in colorectal cancers (17)(18)(19) is likely to be associated with a reduced capacity of the cancer stem cells to differentiate and so to contribute to an increased rate of growth. Studying the patterns of expression of CDX1 and its downstream-regulated differentiation markers, such as KRT20, should therefore enable better characterization of cancer stem cells both in CRC cell lines and in primary CRCs.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…As suggested by Wong et al (19), selection for reduced expression of CDX1 by methylation in colorectal cancers (17)(18)(19) is likely to be associated with a reduced capacity of the cancer stem cells to differentiate and so to contribute to an increased rate of growth. Studying the patterns of expression of CDX1 and its downstream-regulated differentiation markers, such as KRT20, should therefore enable better characterization of cancer stem cells both in CRC cell lines and in primary CRCs.…”
Section: Discussionmentioning
confidence: 94%
“…We have previously shown that the mRNA expression of CDX1 in partially methylated cell lines could be increased by 5-aza-2Ј deoxycytidine treatment and that ''postconfluent'' growth of these partially methylated cell lines, such as LOVO, led to an increase in CDX1 expression that was correlated with a decrease in methylation of a key region in the CDX1 promoter (19). It is now widely accepted that cancer stem cells are the driving cells of a cancer, which will also contain the differentiated cells derived from them (43).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations